DEVELOPMENT OF EFFICIENT REGENERATION AND GENETIC TRANSFORMATION SYSTEMS IN LOCAL CULTIVARS OF CHICKPEA (Cicer arietinum L.) - S. Ali; S. Khan; S. H. Shah; A. Iqbal; M. A. Zia; G. M. Ali (Journal of Animal and Plant Sciences, 2017)
The yield of chickpea in Pakistan is unexpectedly low and unstable that may be due to biotic and abiotic stresses. To combat with these stresses, genetic make of chickpea should be improved incorporating important genes. For successful gene incorporation, an efficient tissue culture system may be established. Therefore, this study was conducted in two local chickpea genotypes namely Bittle-98 and Dasht-2000 for the establishment of an efficient tissue culture system. Among various concentrations of BAP, MS medium fortified with 3.0 mg/l BAP showed the highest multiple shoot formation (69.2 and 70.66%) in cvs Dasht-2000 and Bittle-98, respectively. Similarly, the highest elongation of regenerated shoots (58.33 and 91.66%) was recorded in Bittle-98 and Dasht-2000, respectively on MS media supplemented with 0.25 mg/l IAA. The highest rooting formation (60 and 80%) was recorded in Dasht-2000 and Bittle-98, respectively on MS media having 1.0 mg/l IBA. Half Embryo with single cotyledon was found to be the best explant for genetic transformation. During this study, hygromycin (75 mg/l), acetosyringone (100 µM) and cefotaxime sodium (500 mg/l) were found to be optimum for Agrobacterium-mediated transformation in chickpea. The putative transgenic plants were subjected to GUS and microscopic observations that confirmed the presence of uidA gene in both genotypes. The optimized protocols will provide a base line to improve transformation system and incorporate important genes in chickpea in future research programs.
Keywords: Agrobacterium; Acetosyringone; Cicerarietinum; Genetic transformation